Health Behavior Among Medical Student at Universitas Padjadjaran - Nur Afifah; Sri Yusnita Irda Sari; Miftahurachman Miftahurachman (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Healthy behavior is defined as personal behavior to maintain and improve their health. This includes physical exercise, dietary habit, sleep pattern, stress management, and non smoking behavior, which may greatly contributes to human health. Healthy behavior is essential for medical students as they are becoming future doctors who should advise patients toward healthy lifestyle. This study was conducted to compare healthy behavior between first- and fifth-year medical students.Method: A cross-sectional study was done over 150 medical students of Faculty of Medicine Universitas Padjadjaran (75 first-year students and 75 fifth-year students) between October to November 2013. Data was collected by filling the questionnaire. A scoring mechanism designed to compare healthy behavior between those groups.Results: 75 first and five-year medical students were enrolled in each group. Smoking behavior was more frequent among the fifth-year compared to the first-year students (p=0.013). There were no significant differences in physical exercise (p=0.594), dietary habit (p=0.166) and sleep (p=0.504) between the groups. First year students were more likely to experience mental and emotional stress (p=0.021) than the five-year students. However, there was no significant difference in overall healthy behavior between first-year and fifth-year medical students (p=0.519).Conclusion: Overall healthy behavior is similar between first- and fifth-year medical students. However, in terms of specific behavior, the first-year students tend to be less able to manage mental and emotional stress, whereas smoking is more likely among five-year medical students. Effective intervention needs to be designed to improve healthy behavior among medical students.